(untitled) (Altre Modernità, 2020)
The objective of this work is to identify Fernando Arrabal’s play El arquitecto y el emPerador de ASiria (1966) as an allegory of colonialism and show how this is built upon some elements of the imaginacion de América (Miguel Rojas Mix). Specific tropes, among which are quoted the fountain of youth and the cannibalism, allow to place the play as a transatlantic text that dialogues whit the different discourses of the colonization of America, especially with the chronicles of the explorers of the colonial period. Likewise, different aspects of the American stereotype are updated in a parody of the ethnographic discourse, like the good savage and the acculturated.